ChemInform Abstract: An Efficient Synthesis of Pyrrolo[3′, 2′:4, 5]thiopyrano[3, 2‐b]pyridin‐2‐one: A New Ring System of Pharmaceutical Interest. Issue 11 (8th March 2013) - Barraja, Paola; Diana, Patrizia; Spano, Virginia; Montalbano, Alessandra; Carbone, Anna; Parrino, Barbara; Cirrincione, Girolamo
Abstract Derivatives of the title ring system are screened for their inhibitory activity against 60 human cancer cell lines.